Kajian Sistem Pencahayaan Buatan Antar Ruang Pada Contemporary Art Gallery Taman Mini Indonesia Indah - Ridho Raihan Hanansyah; Astria Melanira (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2024)
The purpose of this study is to determine the quality of lighting that is appropriate for comfort and in accordance with lighting standards. The population of this study is a showroom in the Contemporary Art Gallery Taman Mini Indonesia Indah with a sample of 4 (four) observation points, namely the showroom on the 2nd floor of the Contemporary Art Gallery Taman Mini Indonesia Indah. The method used in this study is descriptive-quantitative method. The results of the study show that the Contemporary Art Gallery Taman Mini Indonesia Indah fully uses artificial lighting without involving natural light. The type of artificial lighting used varies which is placed according to the position and characteristics of the exhibition objects in each room. Some measurement points such as point 1 and point 3 exceed the standards set for the showroom, in addition to observations of the condition of the collection items at various points are also still not in accordance with the standards.